The value of laboratory indicators estimation in patients with metabolically healthy obesity: analysis of a clinical case with literature review - Holubkina, Yevheniia; Skokova, Nataliia; Tykhonova, Tetiana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2022)
Introduction. Obesity currently is a relevant issue of modern medicine due to its global prevalence, heterogeneity of clinical and laboratory manifestations, as well as the association with various comorbid conditions. Depending on the metabolic status, metabolically unhealthy obesity (MUO) and metabolically healthy obesity (MHO) are distinguished. MUO is defined with the presence of criteria for metabolic syndrome (MS) and is associated with an increased risk of cardiovascular and metabolic complications. MHO is characterized by a «metabolically healthy» profile, but the probability of a favorable course of the disease is controversial; many studies indicate the instability of the MHO phenotype and the possibility of further development of MUO. The aim of study: to analyze the features of laboratory indicators associated with MHO and determine the risk factors for the MUO development on the example of a clinical case. Materials and methods. A clinical case of 24 year old female patient diagnosed with alimentary-constitutional obesity class III.  Objectively: height – 174 cm, weight – 124.7 kg, body mass index (BMI) – 41.21 kg/m2, waist circumference – 107 cm, hips circumference – 144 cm; white striae on the abdomen; excessive subcutaneous fat stores, mostly distributed in the abdomen, thighs; blood pressure (BP) – 125/80 mm Hg. Investigation data: hyperleptinemia – 86.82 ng/ml, increased level of HOMA index – 4.6, hyperuricemia – 6.8 mg/dl, vitamin D deficiency – 9.19 ng/ml; lipid profile, fasting plasma glucose, glycated haemoglobin (HbA1c), thyroid stimulating hormone (TSH), triiodothyronine (T3), thyroxine (T4), anti-thyroid peroxidase (anti-TPO) antibodies, cortisol, blood electrolytes, liver function tests – within normal limits. Electrocardiography (ECG), ultrasound of the heart and abdominal organs – without pathology. Results. Normal indicators of lipid metabolism, blood glucose and BP measurement in our patient are characteristic for MHO. However, the combination of hyperleptinemia with insulin resistance, hyperuricemia and vitamin D3 deficiency indicate metabolic and hormonal imbalance and are considered as a risk factors for the development of MS and the further transition of MHO to MUO. Conclusion. MHO should be considered as a transient state, the management of such patients requires careful laboratory monitoring with early detection of metabolic disorders and its adequate and timely correction.